IMPLEMENTATION MULTI-CRITERIA DECISION MAKING FOR SUPPLIER SELECTION ALUMINUM INGOT IN CV. SL - Faqiha, Selvy Athia (FEB Universitas Sam Ratulangi Manado, 2024)
The purpose of this study is to determine the priority order of the criteria, sub- criteria, then determine which suppliers CV SL company can choose. The population in this study is the decision maker and management of CV SL.The sampling technique used was purposive sampling in order to obtain 7 people. The data analysis technique in this study used the Analytical Hierarchy Process (AHP), while the analytical tool used was expert choice 11. The results of the analysis of this study obtained the importance weight of the criteria with the first priority is quality (0.34), price (0.26) , availability (0.15), delivery (0.12), performance history (0.07), warranty & complaint service (0.06). Meanwhile, the results of the assessment of the importance of alternatives in supplier selection show that the LN supplier (0.0786) has the highest weight, the two IS suppliers (0.0760), the three MJ suppliers (0.0733), the four TL suppliers (0.0711), the fifth supplier FI (0.0703), the sixth supplier LM (0.0684). The results of this calculation can be used by the company as a consideration in determining the next supplier selection policy.